Exploring the Effects of Swarm Degradations on Trustworthiness Perceptions, Reliance Intentions, and Reliance Behaviors. (September 2021) - aldin Hamdan, Izz; Capiola, August; Alarcon, Gene M.; Lyons, Joseph B.; Nishimura, Keitaro; Sycara, Katia; Lewis, Michael
Swarms comprise robotic assets operating autonomously through local control laws. Research on human-swarm interaction (HSwI) investigates how human operators collaborate with swarms to accomplish shared goals. Researchers have begun to investigate the role of trust in HSwI, specifically which aspects of robotic swarms affect human trust. Through a human factors lens, the present research builds on earlier HSwI work and investigates the effect of swarm asset degradations on trustworthiness perceptions, reliance intentions, and reliance behaviors. Results showed that trustworthiness perceptions of and intentions to rely on swarms (but not reliance behaviors) were correlated, demonstrating the relation between theoretically relevant antecedents to trust in HSwI contexts. Contrary to past work, the results showed no statistical evidence that asset degradations differentially affect trustworthiness perceptions, reliance intentions, or reliance behaviors. Limitations of the current work (e.g., heterogeneity of post-intervention foraging behavior, sample size) are discussed and followed with future research suggestions.